2023
DOI: 10.54393/pjhs.v4i02.254
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Successful Extubation in Patients with Rapid Shallow Breathing Maximum (RSBImax)

Abstract: Prolonged mechanical ventilation and premature removal from mechanical ventilation (MV) are independent risk factors for morbidity and mortality. Weaning and liberation from MV remain critical stages of a patient's ICU stay. To date, no weaning predictive index has proven to be ideal. Objectives: To determine the frequency of successful extubation in patients on mechanical ventilation after 2 hour of spontaneous breathing trial (SBT). Methods: A total of 100 consecutive patients admitted in Medical ICU, meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…According to this study, mechanical ventilation is most frequently indicated by pneumonia. This is close to a studythat reported 27% patients of pneumonia as an indication of mechanical ventilation [21]. In this study, rate of successful extubation was found to be highest 88.9% in patients with poisoning and this could be due to the fact that the patients with acute poisoning were mostly young and without comorbid.…”
Section: Rabbani B Et Alsupporting
confidence: 88%
“…According to this study, mechanical ventilation is most frequently indicated by pneumonia. This is close to a studythat reported 27% patients of pneumonia as an indication of mechanical ventilation [21]. In this study, rate of successful extubation was found to be highest 88.9% in patients with poisoning and this could be due to the fact that the patients with acute poisoning were mostly young and without comorbid.…”
Section: Rabbani B Et Alsupporting
confidence: 88%